31P nuclear spin singlet lifetimes in a system with switchable magnetic inequivalence: experiment and simulation. Issue 35 (25th August 2021) - Korenchan, David E.; Lu, Jiaqi; Levitt, Malcolm H.; Jerschow, Alexej
Abstract : 31 P NMR nuclear spin singlet order is reported for the first time. Experiments and molecular dynamics simulations indicate that the singlet order relaxes primarily via chemical shift anisotropy at high magnetic field strengths. Abstract : 31 P NMR spectroscopy and the study of nuclear spin singlet relaxation phenomena are of interest in particular due to the importance of phosphorus-containing compounds in physiology. We report the generation and measurement of relaxation of 31 P singlet order in a chemically equivalent but magnetically inequivalent case. Nuclear magnetic resonance singlet state lifetimes of 31 P pairs have heretofore not been reported. Couplings between 1 H and 31 P nuclei lead to magnetic inequivalence and serve as a mechanism of singlet state population conversion within this molecule. We show that in this molecule singlet relaxation occurs at a rate significantly faster than spin–lattice relaxation, and that anticorrelated chemical shift anisotropy can account for this observation. Calculations of this mechanism, with the help of molecular dynamics simulations and ab initio calculations, provide excellent agreement with the experimental findings. This study could provide guidance for the study of 31 P singlets within other compounds, including biomolecules.